Distribution and at-sea activity of a nocturnal seabird, the Bulwer's petrel Bulweria bulwerii, during the incubation period - Dias, Maria P. (2016)
Bulwer'spetrelsarenocturnalseabirdsthatmostlypreyonmesopelagicfauna.Asaerialforagersand shallowdivers,theirfeedingopportunitiesarelimitedbynear-surfaceavailabilityoftheirprey,whichis highlyvariablebothtemporally(reflectingdiurnalandlunarcycles)andspatially.Herewestudiedhow Bulwer'spetrelscopewiththeseconstraintsbyanalysingtheirat-seadistributionandactivityduringthe incubationperiod.Wetrackedthemovementsof20birdsfromSelvagemGrande(NEAtlantic)duringa completelunarcycle,andrecorded30foragingtripsthatlasted11daysonaverage.Birdswereboth distributedaroundthecolonyandinwatersclosetotheAzoreanarchipelago(mid-Atlantic)located 1700kmaway,andweresignificantlymoreactiveatnight(especiallyjustaftersunsetandbeforesunrise), whenmesopelagicfaunaisalsoclosertotheseasurfaceduetotheirdielverticalmigrations.Bulwer's petrelsspentsignificantlymoretime flyingduringmoonlight,althoughtheeffectofthemoonwasrela- tivelyweak(ca.10–15%differencebetweenmoonlitanddarkperiodsofthenight),andnotobviouswhen birdswereforaginginmid-Atlanticwaters,whichwerealsotargetedmoreoftenduringfull-moon.These resultsrevealkeyadaptationsoftheBulwer'spetreltothehighlydynamicecologyofitsmesopelagicprey.